2017
DOI: 10.4244/eij-d-16-00187
|View full text |Cite
|
Sign up to set email alerts
|

How and when to suspect spontaneous coronary artery dissection: novel insights from a single-centre series on prevalence and angiographic appearance

Abstract: SCAD accounts for approximately one third of ACS in young women with ≤1 CRF. The combination of specific angiographic signs and OCT imaging facilitates the diagnosis of ambiguous cases without intimal rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 22 publications
1
71
0
6
Order By: Relevance
“…Correlation with ECG or echo changes and the use of OCT in the 25% of NSTE-ACS patients with angiographically normal epicardial coronary arteries [164][165][166] may be helpful for identifying the culprit lesion, or rule out other mechanisms such as dissection or haematomas [MI with non-obstructive coronary arteries (MINOCA)]. [167][168][169] A routine invasive strategy in NSTE-ACS has been shown to improve clinical outcomes, 170 and benefit was mainly confined to biomarker-positive patients 171 and patients with other high-risk features as defined in Figure 4. Of importance, the use of a radial approach, new-generation DES, and more effective P2Y 12 -inhibitors were not available or broadly implemented in these trials, and led to a magnified benefit in frail ACS populations.…”
Section: Early Invasive Vs Conservative Strategymentioning
confidence: 99%
“…Correlation with ECG or echo changes and the use of OCT in the 25% of NSTE-ACS patients with angiographically normal epicardial coronary arteries [164][165][166] may be helpful for identifying the culprit lesion, or rule out other mechanisms such as dissection or haematomas [MI with non-obstructive coronary arteries (MINOCA)]. [167][168][169] A routine invasive strategy in NSTE-ACS has been shown to improve clinical outcomes, 170 and benefit was mainly confined to biomarker-positive patients 171 and patients with other high-risk features as defined in Figure 4. Of importance, the use of a radial approach, new-generation DES, and more effective P2Y 12 -inhibitors were not available or broadly implemented in these trials, and led to a magnified benefit in frail ACS populations.…”
Section: Early Invasive Vs Conservative Strategymentioning
confidence: 99%
“…A young female patient with single risk factor of cardiovascular disease with ACS presentation should prompt us to rule out SCAD diagnosis. It accounts for approximately one third of young women (<60 years) and with one or less cardiovascular risk factor presenting with ACS [6]. In this particular setting with morphologic ambiguity, OCT which provides high-resolution images, may help to differentiate SCAD from atherosclerotic plaque disruption.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the differentials included an atherosclerotic plaque event resulting in a similar presentation or a Lotus-Root like lesion causing the angiographic findings. Motreff et al, identified 5 angiographic features which could assist clinicians towards the diagnosis of SCAD [16,17]. The patient had 3 out of the 5 criteria fulfilled i.e., absence of atheroma on other arteries, radiolucent flap generating two lumens and ending of angiographic ambiguity on a side branch.…”
Section: Discussionmentioning
confidence: 99%